2020
DOI: 10.1038/s41598-020-59837-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, comorbidity, and breed differences in canine anxiety in 13,700 Finnish pet dogs

Abstract: Behaviour problems and anxieties in dogs decrease their quality of life and may lead to relinquishment or euthanasia. Considering the large number of pet dogs and the commonness of these problematic behaviours, a better understanding of the epidemiology and related molecular and environmental factors is needed. We have here studied the prevalence, comorbidity, and breed specificity of seven canine anxiety-like traits: noise sensitivity, fearfulness, fear of surfaces and heights, inattention/ impulsivity, compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
99
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(139 citation statements)
references
References 65 publications
11
99
1
1
Order By: Relevance
“…A similar trend was also observed in fear of strangers, but the association was not significant. These results are supported by our previous studies: Tiira and Lohi (2015) 22 discovered that younger dogs were generally more fearful, and Salonen et al 17 found that dogs 4-8 years old were most fearful of both dogs and strangers. However, opposite results have also been demonstrated 33,52 .…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…A similar trend was also observed in fear of strangers, but the association was not significant. These results are supported by our previous studies: Tiira and Lohi (2015) 22 discovered that younger dogs were generally more fearful, and Salonen et al 17 found that dogs 4-8 years old were most fearful of both dogs and strangers. However, opposite results have also been demonstrated 33,52 .…”
Section: Discussionsupporting
confidence: 85%
“…Data collection. An online owner-filled questionnaire was designed to collect information on canine behaviour in a pet dog population 17 . The questionnaire was divided into seven main sections based on different behavioural traits, including fear of dogs, strangers, and novel situations (labelled as 'fear'); aggression toward human family members and strangers (labelled as 'aggression'); fear of thunder, fireworks, and gunshot (labelled as 'noise sensitivity'); fear of surfaces and heights; inattention and hyperactivity/impulsivity; separation anxiety; and compulsive behaviour.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations